Marketing in the Industry 4.0—the Usage of Virtual and Augmented Reality - Mitrović, Ksenija; Spajić, Jelena (International Scientific Conference Strategic Management and Decision Support Systems in Strategic Management, 2020)
In the era of Industry 4.0, business is facing significant changes that give digital shape to marketing activities. This transformation is imposed by the conditions in which consumers become digital consumers. In response to the conditions created by the new generation of consumers who have grown up with digital technology, new tools, networking features and social media are being introduced into the world of digital sales and marketing. New technologies are part of innovations that redefine everyday processes and have an impact on the marketing world. Brands often turn to virtual and augmented reality to enhance the communication consumers make with a product, service, or company. Marketing in digital technologies sees a good chance and a tool to bring innovation into its activities and approach to the (potential) consumer. The aim of this research is to examine the level and success of using virtual and augmented reality in marketing activities. A case study method covering Ikea applications was used. The subject of research is the effects of virtual and augmented reality in marketing. Within the topic, a review of the challenges and acceptance of virtual solutions by consumers is given. Research on the applications of new technologies in marketing is becoming increasingly important, especially in the period when Industry 4.0 is revolutionizing business and companies are facing with digital transformation.